2018
DOI: 10.1002/cmr.b.21366
|View full text |Cite
|
Sign up to set email alerts
|

High spatial resolution magnetic resonance imaging of insects covered with a hard exoskeleton

Abstract: The morphological investigation of insects is usually performed using histologic serial sections and subsequent reconstruction of the structures from these sections. The achievement of cross sections for microtomy is time‐consuming and the risk of damaging sections is inevitable. Recently, X‐ray computed tomography (micro‐CT) was used to provide adequate spatial resolution without destroying the specimens. Micro‐CT is limited by the low x‐ray contrast of the insect soft tissues and image quality is relatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Poco tiempo después se comenzó a utilizar este método para el estudio no destructivo ni invasivo en la entomología (Seo, 2018), que demostró tener grandes ventajas para documentar imágenes precisas de la morfología interna de los insectos respecto a las técnicas clásicas que requerían abundantes especímenes para su disección y análisis (Schilling et al, 2012). Con la RMN se hizo posible obtener información y documentar al mismo insecto varias veces para darle seguimiento en diferentes edades durante su desarrollo fisiológico, así como durante etapas fenológicas específicas como el desarrollo de los gametos o durante procesos específicos como la acumulación y flujo de las reservas de energía en función de actividades cotidianas como el vuelo (Favila et al, 2004).…”
Section: Breve Historiaunclassified
“…Poco tiempo después se comenzó a utilizar este método para el estudio no destructivo ni invasivo en la entomología (Seo, 2018), que demostró tener grandes ventajas para documentar imágenes precisas de la morfología interna de los insectos respecto a las técnicas clásicas que requerían abundantes especímenes para su disección y análisis (Schilling et al, 2012). Con la RMN se hizo posible obtener información y documentar al mismo insecto varias veces para darle seguimiento en diferentes edades durante su desarrollo fisiológico, así como durante etapas fenológicas específicas como el desarrollo de los gametos o durante procesos específicos como la acumulación y flujo de las reservas de energía en función de actividades cotidianas como el vuelo (Favila et al, 2004).…”
Section: Breve Historiaunclassified
“…Morphology of adult insects have also been investigated. 8 , 9 Between these two modalities, X-CT is powerful because of its extremely high spatial resolution, but its ionizing radiation is often fatal to the subjects, preventing this modality from aiding in continuous observation.…”
Section: Introductionmentioning
confidence: 99%
“…Their optimal water/lipid content and their size make insects one of the ideal samples for the MRM studies (Hart et al, 2003). Previously, studies on the morphologies of locusts (Gassner and Lohman, 1987), ladybirds (Geoghegan et al, 2000), honey bees (Tomanek et al, 1996), diving beetles (Wecker et al, 2002), fruit flies (Meme et al, 2013) and, more recently, stag beetles (Seo, 2018) have been reported. Several studies were also focused on the development of insects, e.g.…”
Section: Introductionmentioning
confidence: 99%